Assessment of the Heavy Metal Contents in Air Samples Collected from the Area Extended Between Albayda and Alquba Cities (Libya) - Maryam Al-Lambarki; Hamad Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
This study aimed to assess the concentrations of heavy metals, including copper (Cu), iron (Fe), lead (Pb), and zinc (Zn), in air samples collected from five areas in northeastern Libya: Al-Qubbah, Al-Abraq, Lamluda, Shahat, and Al-Bayda. Samples were taken during both summer and winter, with exposure periods of two types: daily and weekly, to examine spatial and seasonal variations and identify potential sources of atmospheric metal pollution. Results revealed significant differences in copper and zinc concentrations between seasons and between study sites. Copper showed a significant increase in winter, especially in Lamluda, where the weekly concentration reached 0.045 µg/ml compared to 0.031 µg/ml in summer (P = 0.0234). Conversely, a decrease was observed in Al-Abraq, from 0.0235 µg/ml (summer, day 1) to 0.019 µg/ml in winter. Zinc showed the greatest seasonal variation, with particularly high levels in winter. In the Abraq area, zinc concentrations increased from 0.167 µg/ml in summer to 0.497 µg/ml in winter (P = 0.0127). Similarly, Lamlouda recorded a sharp increase, reaching 0.460 µg/ml in winter versus 0.029 µg/ml in summer. In contrast, iron and lead were largely undetectable except for a few samples, preventing any robust comparative analysis of these two elements. Spatially, Lamlouda, Abraq, and Al Bayda showed generally higher average concentrations of copper and zinc, which may be related to population density, traffic, and some local industrial activities. These results highlight the need for regular environmental monitoring of heavy metals in the air, especially during winter. ان الهدف الرئيسي من هذه الدراسة هو تقدير تراكيز بعض العناصر وهي النحاس والحديد والرصاص والزنك في عينات تم تجميعها من المنطقة الممتدة ما بين مدينتي البيضاء والقبة بليبيا ، وشملت كلا من مناطق شحات والابرق ولملودة بالإضافة الي البيضاء والقبة وذلك خلال فترات ممتدة من يوم وحتى اسبوع، وخلال فصلي الشتاء والصيف ، وقد بينت نتائج الدراسة ان تراكيز العناصر قيد الدراسة كانت كالاتي : 0.045 µg/ml و 0.031 µg/ml وذلك خلال فصلي الشتاء والصيف على التوالي، بينما كانت تراكيز الزنك خلال الشتاء 0.497 µg/ml ، بينما في الصيف كانت 0.167 µg/ml ، وكانت تراكيز الحديد والرصاص قليلة وغير محسوسة في معظم مواقع الدراسة ، وقد اعزت الدراسة ان وجود العناصر في العينات قيد الدراسة بسبب وجود بعض الانشطة البشرية او الي بسبب عواد المركبات الالية التي تمر بمواقع الدراسة